Peran Paradiplomacy dalam Presidensi G20 Indonesia: Studi Kasus Diplomasi Kota Jakarta pada Urban 20 - Laode Muhammad Fathun (Universitas Diponegoro, 2022)
This article aims to explain the role of paradiplomacy in utilizing the Indonesian presidency in the G20. Using the case study of the Provincial Government of DKI Jakarta, this article argues that the role of DKI Jakarta’s paradiplomacy through city diplomacy has the opportunity to get positive results. This can be seen from the role of Jakarta as an actor in city diplomacy capable of conducting city-level diplomacy at U20. This diplomacy aims to discuss strategic issues at the city level such as mobilization, health, labor, Covid 19 and other issues. With city diplomacy, it is able to become a means of sharing experiences between cities in the world to solve a number of strategic problems at the city level. In addition, Jakarta can play a role as a safe, comfortable place to live through a number of strategic policies, especially in the environmental field. The role of this paradiplomacy through urban diplomacy is a form of motivation, strategy, level of collaboration and level of involvement to assist the central government in solving increasingly complex world problems.